2019
DOI: 10.1103/physrevd.99.044013
|View full text |Cite
|
Sign up to set email alerts
|

Probing the relationship between the null geodesics and thermodynamic phase transition for rotating Kerr-AdS black holes

Abstract: In this paper, we aim to examine the relationship between the unstable circular photon orbit and the thermodynamic phase transition for a rotating Kerr-AdS black hole. On one side, we give a brief review of the phase transition for the Kerr-AdS black hole. The coexistence curve and the metastable curve corresponding to the phase transition are clearly shown. On the other side, we calculate the radius and the angular momentum of the unstable circular orbits for a photon by analyzing the effective potential. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 107 publications
3
19
0
Order By: Relevance
“…In particular, these changes have an universal exponent 1 2 near the critical point. Later, the study is extended to other black holes and gravity theories, for example rotating case [51], Gauss-Bonnet case [52], massive gravity case [53] and Born-Infeld case [54], which confirm the relations further. See also Ref.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…In particular, these changes have an universal exponent 1 2 near the critical point. Later, the study is extended to other black holes and gravity theories, for example rotating case [51], Gauss-Bonnet case [52], massive gravity case [53] and Born-Infeld case [54], which confirm the relations further. See also Ref.…”
Section: Introductionsupporting
confidence: 53%
“…Combing these results, we confirm the conclusion of Refs. [50,51] that there is a close relation between photon orbits and phase transitions, and the photon orbit radius and the minimum impact parameter can be used as order parameters to describe BH phase transitions. Nevertheless, we should point out zeroth-order and first-order phase transitions can not be distinguished with photon orbits alone.…”
Section: Discussionmentioning
confidence: 99%
“…Further calculation also showed that these changes of the radius and the minimal impact parameter have a universal critical exponent 1 2 , which implies that these changes can serve as an order parameter to describe the small-large black hole phase transition. Subsequently, we extended our study to the rotating Kerr-AdS black holes [34]. Even when the black hole gets rotation, our result shows that the similar relationship between the photon ring and the phase transition also holds.…”
Section: Introductionmentioning
confidence: 61%
“…As shown in Refs. [33,34], such behavior of T reveals that no VdW-like phase transition exists. When b=0.4 and 0.45, the results are described in Figs.…”
Section: B Phase Transition and Photon Spherementioning
confidence: 93%
See 1 more Smart Citation